Prevalence and associated factors of perinatal asphyxia among newborns in Dilla University referral hospital, Southern Ethiopia– 2017 - Alemu A; Melaku G; Abera GB; Damte A (Dove Medical Press, 2019)
Abebe Alemu,1 Getnet Melaku,1 Gerezgiher Buruh Abera,2 Ashenafi Damte21Department of Midwifery, College of Health Science and Medicine, Dilla University, Dilla, Ethiopia; 2Department of Nursing, College of Health Sciences, Mekelle University, Mekelle, Tigray, EthiopiaBackground: Globally, perinatal asphyxia is a significant contributing factor for neonatal morbidity and mortality. Thus, this study was aimed to assess the prevalence and associated factors with perinatal asphyxia among newborns in Dilla University referral hospital.Methods: A cross-sectional study was conducted among newborns in Dilla University referral hospital, Ethiopia from February to April 2017. Systematic random sampling techniques were used to enroll a total of 262 study subjects. Multivariate logistic regression analysis was used to identify factors associated with the perinatal asphyxia among newborns.Result: Of the newborns, 32.8% had perinatal asphyxia, and factors associated significantly were anemia during pregnancy (adjusted OR=2.99, 95%CI: 1.07–8.35), chronic hypertension (adjusted OR=4.89, 95%CI: 1.16–20.72), meconium-stained amniotic fluid (adjusted OR=3.59, 95%CI: 1.74–7.42), and low birth weight newborns (adjusted OR=3.31, 95%CI: 1.308–8.37).Conclusion: Maternal anemia during pregnancy, chronic hypertension, meconium stained amniotic fluid, and low birth weight were significantly associated with perinatal asphyxia. Therefore, early screening and appropriate intervention during pregnancy, and intrapartum might reduce perinatal asphyxia among newborns.Keywords: perinatal asphyxia, newborn, Dilla, Ethiopia